Pengaruh Prosedur Pemungutan, Penyetoran, Dan Pelaporan Pajak Penghasilan (Pph) Pasal 22 Terhadap Penurunan Omset Penjualan Pada Pt Duta Intidaya, Tbk - Tia Damayanti, Tia Damayanti; Bambang Santoso, Bambang Santoso (Cakrawala Akuntansi & Manajemen, 2024)
This study explains that the Deposit Collection Procedure has an effect on decreasing sales turnover. This study explains that Article 22 Income Tax Reporting (PPH) has an effect on decreasing sales turnover. This study explains whether Article 22 Income Tax Collection and Reporting Procedures have an effect on decreasing sales turnover. This research used a simple random sampling data collection technique. This research was conducted at the location of PT Duta Intidaya, Tbk on Jalan Danau Sunter Utara No.Kav.II, RT14/RW13, Sunter Agung, Tanjung Priok, North Jakarta, Jakarta 14350, North Jakarta. The sample in this study were 78 employees who worked at PT Duta Intidaya, Tbk. The results of this study explain that the Deposit Collection Procedure has a positive and significant effect on reducing sales turnover. This study explains Article 22 Income Tax Reporting (PPH) has a positive and significant effect on reducing sales turnover. Article 22 has a positive and significant effect on the decline in sales turnover. Managerial implications was explained that it is expected to pay attention to and understand the effect of Article 22 Income Tax and VAT (Domestic, Import, Other Income) on Tax Revenue at the North Jakarta Primary Tax Service Office. Every year a more significant increase can be obtained so that it can increase Tax Revenue, especially for PPh Article 22 compared to the contribution of Tax Revenue at the North Jakarta Primary Tax Service Office.